Analysis of a National Biosafety system: Regulatory Policies and Procedures in Argentina - Burachik, M.; Traynor, Patricia L. (International Service for National Agricultural Research, 2002)
Biosafety is achieved by assessing and managing environmental and health risks of new technologies, evaluating the potential ecological and health consequences, and weighing these against potential benefits. During the past decade, national biosafety systems have gained importance as mechanisms for ensuring the safe use of biotechnology products without imposing unacceptable risk to human health or the environment, or unintended constraints to technology transfer. This country report presents an analysis of the development and present status of the biosafety system in Argentina; South America; and its impact on the commercialization of genetically modified organisms. Findings and recommendations in the report may serve as the basis for discussions to strengthen and adapt the biosafety system to the changing context for biotechnology products in Argentina; South America; . They may also serve to advance efforts in the areas of public acceptance, technology transfer and regulatory harmonization.